COMPARATIVE ANALYSIS OF CONSUMER EMOTIONS ON MULTI-LEVEL MARKETING BETWEEN ADULT AND YOUTH IN MANADO - Kasenda, Daniel; Lapian, Joyce S.L.H.V.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
As we know that multi-level marketing business is popular among Indonesian people, where the system of that business type is offering a multiple source of income by selling the product simultaneously. Multilevel marketing business is offering a second profit option that the member of the company can gaining more profit by recruiting a new member. The main purpose of this research is to find out the difference of the consumer emotion from youth and adult people on multilevel marketing business. This research used quantitative research methods that will describe and explore the role of social media and mobile usage to e-commerce in small medium enterprise and its customer. The result showed that sad, anger, disgust, surprise, emotions are no significant differences between the youth and adult towards multi-level marketing experiences, and there are significant differences for enjoy and fear emotions. From the conclusion above, the suggestions for multi-level marketing business that enjoy and fear needs to be considered as the main factor to approach customer and for surprise, disgust, anger and sad emotions not recommended to approach customer.Â Keywords: comparative analysis, consumer emotion, adult and youth people